Interactive Muon Catalyzed and Intertial Confinement Fusion - Cripps, Ronald Gregory (My University, 1993)
Energetic viability calculations of nuclear fusion energy systems based on two distinct approaches to a symbiotic combination of Muon Catalyzed Fusion (µcf) and Inertial Confinement Fusion (ICF) have been performed. The first approach involves a deuterium-tritium ICF pellet ignited by muon catalyzed fusion heating; the second approach is based on the energy generated by µCF reactions in deuterium-tritium compressed to high density. Viability evaluations rely upon modeling of identified critical energy gain parameters for energy systems based upon each of the µCF-ICF system and developing muon catalyzed reaction models in conditions found in high density compressions. An energy system based on µCF in compressed deuterium-tritium was found to be non-viable due primarily to the sharp decrease in the muon induced fusion rate for temperatures greater than 40 eV. The viability of a fusion energy system based on the µCF triggered spark ignition is favorable provided that technology can be developed which allows for the deposition of sufficient quantities of muons into a very small volume within a very short duration.
Keywords: Engineering; Nuclear Engineering; Engineering